Pseudo-Hermitian Hamiltonians generating waveguide mode evolution - Chen, Penghua (2018)
We study the properties of Hamiltonians defined as the generators of transfer matrices in quasi-one-dimensional waveguides. For single- or multimode waveguides obeying flux conservation and time-reversal invariance, the Hamiltonians defined in this way are non-Hermitian, but satisfy symmetry properties that have previously been identified in the literature as “pseudo-Hermiticity” and “anti-PT symmetry”. We show how simple one-channel and two-channel models exhibit transitions between real, imaginary, and complex eigenvalue pairs.